Plasma Extracellular Vesicle Size and Concentration Are Altered in Alzheimer’s Disease, Dementia With Lewy Bodies, and Frontotemporal Dementia - Longobardi, Antonio; Benussi, Luisa; Nicsanu, Roland; Bellini, Sonia; Ferrari, Clarissa; Saraceno, Claudia; Zanardini, Roberta; Catania, Marcella; Di Fede, Giuseppe; Squitti, Rosanna; Binetti, Giuliano; Ghidoni, Roberta (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer’s disease (AD), Frontotemporal dementia (FTD), dementia with Lewy bodies (DLB) are the three major neurodegenerative dementias. In this study we provide evidence that an alteration in extracellular vesicles (EVs) release is common across the three most common neurodegenerative dementias, AD, DLB and FTD. Specifically, we analyzed plasma EVs in three groups of patients affected by AD, DLB and FTD, and we found a significant reduction in EVs concentration and larger EVs size in all patient groups. We then investigated whether the loss of a neurotrophic factors is also a common pathogenic mechanism among FTD, DLB and AD and if levels of neurotrophic factors might affect EVs release. Plasma levels of progranulin and cystatin C (CysC) were partially altered; however, taking together all variables significantly associated to the diagnostic groups only EVs size and concentration were able to distinguish patients from controls. The diagnostic performance of these two EVs parameters together (ratio) was high, with a sensitivity of 83.3% and a specificity of 86.7%, able to distinguish patients from controls but not to differentiate the different forms of dementias. Among the candidate neurotrophic factors, only CysC levels were associated with EVs concentration. Our study suggests that an alteration in the intercellular communication mediated by EVs might be a common molecular pathway underlying neurodegenerative dementias. The identification of shared disease mechanisms is of pivotal importance to develop treatments to delay disease progression. To this aim, further studies investigating plasma EVs size and concentration as early biomarkers of dementia are required.